Hubungan Pengetahuan Ibu Tentang Posyandu Dengan Keaktifan Mengikuti Posyandu Di Desa Kare Kabupaten Madiun - Khoiriyah, Antik, Siti Arifah, S.Kp., M.Kes, Ambarwati, S.pd., M.Si (2015)
Posyandu is one of the form of healt effort Community managed from, by and for people with technical support from health workers that the targets were the entire community. The scope of children weighing in Indonesia in 2013 by 80.30%. While in 2012 the scope of this is lower, namely by 75%. Achievement in the year 2013 enough qualified by the target of 80%, but although they meet the target of these children weighing on the following year is expected to more robust than the previous year. This study purpose is to understand the relation of posyandu knowledge with following the Posyandu Kare village in Madiun district. The research used quantitative method. The design of this research was descriptive correlative with the approach of cross sectional. The population in this research was all mom toddlers posyandu participants listed in Posyandu Kare from 8 Posyandu who were found in the village working area Kare Puskesmas Kare Madiun district County with 397 participants as much as mothers and study sample namely 80 respondents who determined with technique cluster random sampling. Research instrument in the form of a questionnaire. Data Analysis using the results of research Fisher Exact Test . Calculations yield ρ value of 0.005. Because the value of ρ <0.05 it was decided that H0 is rejected and Ha accepted. Conclusions : In this study there is a relationship with the mother's knowledge of Posyandu activeness followed Posyandu in the village Kare Madiun.